Does Dual Banking System in Indonesia Differentiate Investment Account Requirement? - Yaser Taufik Syamlan (Institute for Research and Community Empowerment (LPPM TAZKIA), 2017)
Abstract. This paper aims to propose a model of investment account based on Islamic Financial Services Board guiding principles. The research figures out some factors affecting the process of deploying investment account, the proposed model, cost - benefit analysis as well as the steps to be taken by Islamic banking stakeholders to install the model in the future. Having reviewed many litetatures related to irregular deposit, investment account as well as the institutional theory, the study found that the adoption of investment account heavily relies on the political factor applied by Bank Indonesia. Law No. 21 Year 2008 that regulates Indonesian Islamic Banking clause 35 stated that Bank Indonesia has coercive power to drive the accounting and governance standard for the Indonesian Islamic banking. Other actors such as Financial Services Authority, National Sharia Board, and Indonesia Deposit Insurance Corporation also do affect the regulation on Investment Account. This paper informs the policy makers to set different regulation on investment account within the practice of dual banking system.